Development of an optical micro-motion sensing system - Kwan, Wei Xiang. (2013)
Physiologic hand Tremor is a common trait among humans although it varies in amplitude and frequency from individuals to individuals. It is generally unnoticeable as its amplitude is small. The amplitude of hand tremor can worsen due to anxiety, fatigue or use of stimulants like caffeine. However, it is a big factor limiting the effectiveness of microsurgery performed by microsurgeons. Microsurgery is usually performed under the microscope and gave the surgeons no force feedback. A steady hand that moves with high precision is desired for microsurgery.